(untitled) (Patan Pragya, 2021)
The present article explores the expression of the protest and voices of the Dalits on the basis of poems written on the Dalit issues and subjects. It also examines how Dalits as subalterns speak for the causes against their discrimination, exploitation and socio-political exclusion. Poetry is an appropriate medium to express the feelings and socio-political reality of our society; so as protest poetry portrays the Dalit problems in general, and rigorously upholds the rights, equality, dignity and social liberation. The findings of the article show that the poetic features, messages and themes are expressed as the voices of the subalterns with pain, anger and revolt. The poetry raises the voice for justice and liberation; and also encourages the Dalits to move against the discrimination. The protest poetry questions the credibility and validity historiography of the Dalits and asks for compensation against centuries-long discrimination and exclusion. The article is developed based on the selected poems of Aahuti and Harisharan Pariyar by critically analyzing them from subaltern perspective.